Історія вівтарів Кирилівської церкви Києва ХІІ–ХІХ ст. - Марголіна, І. (Сiверянський літопис, 2025)
Метою публікації є впровадження до наукового обігу нових відомостей про приділи Кирилівської церкви. На основі виявленої інформації створити мапи приділів Кирилівської церкви в Києві протягом ХІІ–ХІХ ст. Припущення, висновки, нові відомості, на нашу думку, мають безперечну наукову новизну. Методи дослідження застосовано відповідно до поставленої мети на основі принципів об’єктивізму та науковості. Переважно використано метод аналізу, індукції та дедукції, архівного пошуку. Висновки: у результаті дослідження віднайдено інформацію про наявні в храмі протягом ХІІ–ХІХ ст. приділи й вівтарі. Розроблено схеми розміщення престолів на першому та другому поверсі церкви. Віднайдено свідчення щодо опорядження приділів, з’ясовано, де було облаштовано печі для опалення теплих приділів. Це доповнило знання про історію Кирилівської обителі в Києві – унікальної пам’ятки ХІІ ст. The purpose of the publication is to introduce into scientific circulation new information about the aisles of the Cyril church during the 12th–19th c. On the basis of the revealed information, we aim to create a map of the aisles of St Cyril church in Kyiv. Assumptions, conclusions, new information on this issue, in our opinion, have indisputable scientific novelty. The research methods were applied in accordance with the set goal based on the principles of objectivism and scientific research. The method of analysis, induction and deduction, archival search was mainly used. Conclusions: as a result of the research, information was found about the aisles and altars in the temple during the 12th–19th c. Plans for placing thrones on the first and the second floors of the church have been developed. Evidence was found regarding the arrangement of the allotments, it was found out where the stoves for heating the warm allotments were installed. This added to the knowledge of the history of the Cyril monastery in Kyiv – a unique monument of the 12th c.